Analysis of organic pollutants in water samples of White Drin, Black Drin and Fierza Reservoir - Nuro, Aurel; Marku, Elda; Murtaj, Bledar (Journal of Engineering & Processing Management, 2017)
This study presented data about concentrations of some organic pollutants in Albanian part of Black Drin (BD), White Drin (WD) and Fierza Reservoir (FR). Thirteen stations were analyzed in this study. Sampling of water was realized in May 2017. Drin River presents important aquatic area in Albania. For all water samples were analyzed organochlorine pesticides (OCPs), polychlorinated biphenyls (PCBs), benzene, toluene, ethylbenzene and o-, m-, p-xylenes (BTEX) and polyromantic hydrocarbons (PAH). Organochlorined pesticides and PCBs were found in higher level for Fierza Reservoir stations. Their concentrations for Black and White Drin samples were 5-10 times lower.